A study of the numinous presence in Tennyson's poetry - Louw, Denise Elizabeth Laurence (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1985)
From Preface: A reader looking to this study for a charting of the diverse religious views held by Tennyson at different periods in his life may be disappointed. My primary concern has been not with religious forms, but with the numinous impulse. However, though I approached the topic with a completely open mind, I find my own Christian convictions have been strengthened through the study of Tennyson's poetry. As the title indicates, I have not attempted to deal with the plays. To explore both the poetry and the plays in a study of this length would have been impossible. I have perhaps been somewhat unorthodox in attempting to combine several disciplines, especially since I cannot claim to be a specialist in the areas concerned. However, I felt it necessary to approach the subject from a number of points of view, and to see to what extent the results could be said to converge on some sort of central "truth". When I have despaired of being able to do justice to a particular aspect within the imposed limits, I have sometimes found comfort in the words of Alan Sinfield (The Language of Tennyson's "In Memoriam", p.211): "We can only endeavour continually to approach a little closer to the central mystery; the ma j or advances will be infrequent, but most attempts should furnish one or two hints which others will develop. "
Keywords: Tennyson, Alfred Tennyson, Baron, 1809-1892 -- Criticism and interpretation; English poetry -- 19th century -- History and criticism